ISOLATION OF ASP TOXIN-PRODUCING NITZSCHIA FROM THAILAND - Romero, M. L.J.; Lirdwitayaprasit, T.; Kotaki, Y.; Lundholm, N.; Relox Jr., J.; Furio, E. F.; Terada, R.; Yokoyama, T.; Kodama, M.; Fukuyo, Y. (Marine Research in Indonesia, 2008)
Nitzschia navis-varingica is recognized as the major ASP toxin producer other than Pseudo-nitzschia species. Surveys on the distribution and the toxin production of this diatom has been conducted in a few countries in eastern Asia and expanded to Thailand. Eighteen isolates from Thailand showed the positive result for the ASP toxin production is DA and IB, although the ratio of IB was much lower than those of the isolates from southern countries including Okinawa, Japan, the Philippines and Vietnam.